Nove metode zdravljenja okvar hrbtenjače - Šavrin, Rajmond (Rehabilitacija (Ljubljana), 2009)
The author describes the possibilities of the treatment of spinal cord injury (SCI) patients from the ancient times to the present as well as some new treatment methods for the improvement of spinal cord regeneration. It can be said that the history of the SCI treatment was not too successful but its present is creative and its future promising. In the past, the possibilities for the treatment of SCI patients were very limited. In the present time, there are numerous therapeutic and diagnostic methods for improving the health of SCI persons and great emphasis is placed on prevention methods. Many current clinical trials promise that we can expect the solution to the problems of spinal cord regeneration in the near future.
Keywords: Hrbtenjača, poškodbe; Spinal Cord Injuries; vocational rehabilitation; rehabilitacija; rehabilitation; spinalna okvara; hrbtenjača; poškodbe; therapy; zdravljenje